Analysis of the academic offerings in higher education in the southern region of the Sucre department in relation to the productive potential of the region and the vocational preferences of its inhabitants. (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2021)
The research aimed to analyze the academic offerings provided by higher education institutions (HEIs) located in the southern region of the Sucre department in the Colombian Caribbean region, contrasting them with the productive potential and vocational preferences of its inhabitants to determine how much this offering contributes to development as important and active actors within the department. In this way, the degree of relevance of the training offering to develop the productive potential of the region was identified. The research consisted of three specific objectives that allowed for the analysis of the characteristics and productive potential of the area, the academic offerings created for the municipalities in the southern region of the Sucre department, and the relevance from the perspective of residents, leaders, academic experts, and entrepreneurs. A descriptive quantitative and qualitative research approach was conducted to identify characteristics of the study problem and describe them for analysis. Finally, it was established that the academic offering in the Sucre department does not meet the needs of the productive potential, leading to gradual productive development in one of the country's departments with the greatest agricultural potential.